The Role of the Environmental Service in the Management of Hazardous and Toxic Waste (B3) in Karangligar Village - Amaey, Amaey; R, Yuniar; A, Muhamad (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
Management of Hazardous and Toxic Materials (B3) waste in Karangligar Village is an important issue in maintaining environmental sustainability. Law Number 32 of 2009 regulates the obligation to manage B3 waste, but practices in the field still face various challenges. This study uses an empirical legal approach by collecting primary data through interviews, as well as secondary data from legal documents and related literature. The results of the study indicate that the Role of the Karawang Regency Environmental Service (DLH) in Karawang Regency Regional Regulation Number 14 of 2012 concerning Environmental Protection and Management Article 53 Paragraph (1) Environmental supervisory officers are authorized to monitor, request information, make copies of documents and/or make necessary notes, enter certain places, take pictures, make audio-visual recordings, take samples, check equipment, check installations and/or transportation equipment, and/or stop certain violations. The steps taken by the Karawang Regency Environmental Service (DLH) in handling the case of the disposal of Hazardous and Toxic Materials (B3) waste in Karangligar Village are in accordance with the provisions of applicable regulations, as stipulated in Karawang Regency Regional Regulation Number 14 of 2012. These steps include location identification, mapping, sampling, and environmental restoration efforts.